Building volumetric maps with cooperative mobile robots and useful information sharing : a distributed control approach based on enthropy - Rocha, Rui Paulo Pinto da (2006)
Tese de doutoramento em Engenharia Electrotécnica e de Computadores apresentada à Faculdade de Engenharia da Univ do Porto